Synthesis of Moore FSM with expanded of coding space for telecommunication systems - Barkalov, A. A.; Titarenko, L. A.; Hebda, O. P. (Проблеми телекомунікацій, 2011)
The proposed method is targeted on reduction of hardware amount in logic circuit of Moore finite-state machine implemented with customized matrices. The method is based on using more than minimal amount of variables in codes of FSM internal states.
Keywords: Moore FSM; graph-scheme of algorithm; pseudoequivalent states; customized matrices